ANALYSIS OF RAW MATERIAL INVENTORY CONTROL USING THE ECONOMIC ORDER QUANTITY (EOQ) METHOD IN DETERMINING THE PERIODIC ORDER QUANTITY (POQ): CASE STUDY AT CV. TAHU BANDUNG NN - Lulu Rohana; Ade Kurniawan; Diyah Astuti Ningsih; Amellia Putri Septiana; Aprilia Dwi Aisyah (Samudra Publisher, 2024)
The preparation of the raw material budget at CV. Tahu Bandung NN was made with the aim of knowing the management of merchandise inventory to maximize the cost of raw material requirements. This preparation is basically the same as the purpose of preparing the raw material budget in general. This preparation is a management plan for profit from sales and maintaining product quality. This research aims to find out how to control raw material inventory carried out by the Tofu Factory by analyzing how to control raw material inventory using the Economic Order Quantity (EOQ) and Periodic Order Quantity (POQ) methods. In this research we used a descriptive-qualitative approach. The author uses observation, interviews and documentation in collecting data. The resource persons in this research consisted of factory owners and employees at the Tofu Factory. The results of the research show that based on company policy, it uses traditional methods by ordering 12,500 kg of raw materials, while using the EOQ/POQ method it uses 10,560 kg. The frequency of purchasing soybean raw materials was previously 4 orders in 1 month. In the traditional way of Rp. 1,335,000, while using the EOQ/POQ method the total inventory cost is Rp. 958,125/month.